2023
DOI: 10.1111/bjh.18841
|View full text |Cite
|
Sign up to set email alerts
|

CD30 as a therapeutic target in adult haematological malignancies: Where are we now?

Abstract: Summary CD30 is a transmembrane protein from the tumour necrosis factor receptor superfamily. It is expressed on a small subset of activated T and B lymphocytes, and various lymphoid neoplasms. CD30 is a particularly interesting treatment target because its levels are high in tumours but low in healthy tissues. Several therapeutic strategies targeting CD30 have been developed, including monoclonal antibodies, conjugated antibodies (combination of brentuximab vedotin with chemotherapy or immunotherapy), bispeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
3
0
2
Order By: Relevance
“…In all but 1 case, it occurred together with the p terminal deletion of 1p36; however, its emergence as a sole event in patient #16 points to a potential role in pathogenesis. The region encompasses the coding sequences of MTOR , TNFRSF8 ( CD30 ), and TNFRSF1B , which are described to have an activating role in a majority of other lymphomas, 26 , 27 , 28 potentially suggesting a pleiotropic effect of these genes in lymphomagenesis. This has already been described regarding TNFRSF8, which has subtype-specific effects on the growth of T-cell and B-cell lymphoma cell lines, 29 as well as mTOR activity, which is restricted to ABC DLBCL-s in most of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…In all but 1 case, it occurred together with the p terminal deletion of 1p36; however, its emergence as a sole event in patient #16 points to a potential role in pathogenesis. The region encompasses the coding sequences of MTOR , TNFRSF8 ( CD30 ), and TNFRSF1B , which are described to have an activating role in a majority of other lymphomas, 26 , 27 , 28 potentially suggesting a pleiotropic effect of these genes in lymphomagenesis. This has already been described regarding TNFRSF8, which has subtype-specific effects on the growth of T-cell and B-cell lymphoma cell lines, 29 as well as mTOR activity, which is restricted to ABC DLBCL-s in most of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Brentuximab vedotin was an antibody-drug conjugate made of a humanized chimeric antibody directly against CD30 covalently bound to a potent microtubule disruptor via a linker that can be cleaved by proteases. The drug could bind to the membrane receptor of CD30, forming a complex with the anti-CD30 drug and enters the cell through receptor-mediated endocytosis, and then the complex fuses with lysozyme, resulting in the aforementioned linker being cleaved by proteases, releasing free drugs in the cytoplasm 59 , 60 . Phase I and II studies in adults with relapsed/refractory CD30+lymphomas, including ALCL, demonstrated the safety and efficacy of brentuximab vedotin, leading to FDA approval for relapsed/refractory ALCL in adults and successful incorporation into frontline therapies 61 .…”
Section: Discussionmentioning
confidence: 99%
“…CD30 is a transmembrane protein from the tumor necrosis factor receptor superfamily and is expressed on activated T and B lymphocytes and in various lymphoid neoplasms [39]. The CD30 antigen is highly expressed on neoplastic cells in hematological malignancies such as DLBCL, representing an ideal immunotherapeutic target [40].…”
Section: Cd30mentioning
confidence: 99%